THE PHENOMENON OF IMPULSE BUYING IN E-COMMERCE: THE ROLE OF SOCIAL MEDIA MARKETING, INFLUENCER REPUTATION, AND PRICE DISCOUNTS ON SHOPEE - Eko Djo; Haryo Kusumo; Edwin Zusrony (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Impulse buying refers to an action of purchasing a service or product without prior planning. An emotion over a long period of time about a particular service or product, or influence from other products, can serve as triggers to make such purchases. The purpose of this research is to study the effect of social media marketing, influencer's reputation, and price discounts related to the application of Shopee on Impulse Buying Behavior of Generation Z in Semarang Regency, especially Ungaran Subdistrict. This research employs a quantitative approach where social media marketing, influencer's reputation, and price discount serve as independent variables while Impulse Buying is the dependent variable. The respondents in this case are limited to generation Z, with a total sample size of 50. Data collection employs questionnaires evaluated on five parameter likert scales. The data collected were analyzed using multiple linear regression analysis which was processed with SmartPLS 4.0 software for data processing and was executed in two steps: outer model and then inner model. The tests were conducted through the steps discriminant validity, composite reliability, classic assumption testing, hypothesis testing, t-test, and F-test. It has been found that the independent factors Social Media Marketing, Influencer's Reputation, Price Discount have a positive and significant impact on the dependent factor of Impulse Buying. From testing the F test we also found that the independent factors of Social Media Marketing, Influencer's Reputation, Price Discount also have a simultaneous impact on the dependent factor Impulse Buying.